2010
DOI: 10.1100/tsw.2010.80
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of Some Aquatic Hyphomycetes against Plant Pathogenic Fungi

Abstract: The antagonistic activity of five aquatic hyphomycetes, viz., Heliscus lugdunensis, Tetrachaetum elegans, Tetracladium breve, T. marchalianum, and T. nainitalense, against seven plant pathogenic fungi was studied using a dual culture technique. Inhibitory activity of tested aquatic hyphomycetes was determined by measuring the radial growth of plant pathogenic fungi on dual culture plates. Tetrachaetum elegans showed antagonistic activity against Colletotrichum falcatum, Fusarium oxysporum, Pyricularia oryzae, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Gulis and Stephanovich [ 21 ] found the growth inhibition of some bacterial and pathogenic fungal strains by using freshwater hyphomycetes, including A. longissima . Recently, Sati and Arya [ 22 ] and Arya and Sati [ 13 ] also reported antimicrobial potential of five freshwater hyphomycetes against seven pathogenic fungi and five bacteria. Xiao et al [ 23 ] isolated antimicrobial compounds from the fungus Pestalotiopsis photiniae and evaluated inhibitory potential of this fungus against some plant pathogenic fungi.…”
Section: Resultsmentioning
confidence: 99%
“…Gulis and Stephanovich [ 21 ] found the growth inhibition of some bacterial and pathogenic fungal strains by using freshwater hyphomycetes, including A. longissima . Recently, Sati and Arya [ 22 ] and Arya and Sati [ 13 ] also reported antimicrobial potential of five freshwater hyphomycetes against seven pathogenic fungi and five bacteria. Xiao et al [ 23 ] isolated antimicrobial compounds from the fungus Pestalotiopsis photiniae and evaluated inhibitory potential of this fungus against some plant pathogenic fungi.…”
Section: Resultsmentioning
confidence: 99%
“…While several studies have reported inhibitory effects of aquatic hyphomycetes on bacteria and fungi (e.g. Gulis and Stephanovich, 1999;Sati and Arya, 2010) and chemical inhibition among aquatic hyphomycetes (Shearer and Zare-Maivan, 1988;Treton et al, 2004;Ferreira et al, 2010) or between aquatic hyphomycetes and cooccurring bacterial strains (Gulis and Suberkropp, 2003), the allelopathic effect of aquatic hyphomycetes on stream PP has, to our knowledge, never been studied. Our results show that most of the aquatic hyphomycete species tested (8 out of 12 tested in solid cultures) inhibited at least one diatom species.…”
Section: Discussionmentioning
confidence: 96%
“…HELU was the most antagonistic species, particularly the S strain in reference conditions. Although some studies claim stronger allelopathic interactions for TEMA than for HELU, a clear inhibitory activity of this latter towards other AH species was previously recognized [40,63]. This trait, combined with high growth rates, may be responsible for its dominance in both mixed assemblages in the decomposition test (S medium).…”
Section: Discussionmentioning
confidence: 97%